Vairagya and adaptability as psychological buffers: yogic perspective on coping with grief and loss - J., Sridevi K. (International Journal Of Community Medicine And Public Health, 2025)
Grief is a profound and universal human experience, yet its expression and management are deeply shaped by cultural, psychological, and spiritual factors. Traditional models such as the Kübler-Ross stages and the dual process model have contributed to understanding bereavement, but they often lack the transpersonal dimension that many individuals rely on for healing. Yogic philosophy, particularly the principles of Vairagya (detachment) and adaptability (psychological flexibility), offers valuable complementary perspectives for coping with loss. Vairagya provides an inner anchor through balanced detachment, allowing individuals to acknowledge sorrow without becoming consumed by it, while adaptability supports adjustment to new realities and fosters resilience in the aftermath of change. Together, these concepts create a dual framework that promotes emotional regulation, cognitive flexibility, and post-traumatic growth. Contemporary evidence indicates that yoga, mindfulness, and related practices enhance resilience, reduce rumination, and strengthen coping capacity, aligning closely with these philosophical ideals. Community-level applications, including yoga-based grief support programs and collective rituals, further highlight the potential for integrating these approaches into culturally sensitive mental health strategies. By synthesizing insights from psychology, yogic philosophy, and therapeutic practice, this paper underscores the transformative potential of Vairagya and adaptability in navigating grief, offering an integrated model that bridges ancient wisdom with modern clinical relevance.